Study Optimization of Power Transformer Using Artificial Intelligence Technique: Exploring the Potential of AI Techniques for Power Transformer Optimization (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Transformers are the core of electrical transmission and appropriation frameworks. The point of transformer design is to acquire the elements of all pieces of the transformer so as to flexibly these information to the producer. The transformer ought to be designed in a way with the end goal that it is monetarily suitable, has low weight, little size, great performance and simultaneously it ought to fulfill all the imperatives forced by worldwide gauges. Numerous specialists have utilized Artificial Intelligence (AI) methods for transformer design optimization (TDO) and performance investigation. Be that as it may, the genuine capability of AI strategies is yet to be completely investigated for TDO issues. This paper leads a short survey of innovative work in the field of transformers utilizing customary optimization strategies, man-made brainpower based optimization methods and recommends a portion of the new bio-roused AI procedures that can be utilized for TDO issues